1994
DOI: 10.1177/0093854894021001004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cognitive-Behavioral Treatment on Sex Offender Recidivism

Abstract: Preliminary results from a longitudinal study of the effectiveness of cognitive-behavioral treatment with sex offenders are presented. The study's research design includes three groups: a treatment group, a volunteer control group (those who volunteered for but did not receive treatment), and a nonvolunteer control group (subjects who refused the opportunity for treatment). Although the treatment group had the lowest reoffense rates for both sex and other violent crimes, main effects analyses did not yield con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
171
2
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(180 citation statements)
references
References 18 publications
6
171
2
1
Order By: Relevance
“…Of the studies that compared treated to untreated subjects, two programs presented lower recidivism rates for treated subjects (87,89,90), and two programs showed no differences (78,91).…”
Section: Outcome Studies Of Cognitive-behavioral Treatmentmentioning
confidence: 97%
See 1 more Smart Citation
“…Of the studies that compared treated to untreated subjects, two programs presented lower recidivism rates for treated subjects (87,89,90), and two programs showed no differences (78,91).…”
Section: Outcome Studies Of Cognitive-behavioral Treatmentmentioning
confidence: 97%
“…As Table 3 shows, recidivism rates from cognitive and behavioral treatment programs that have been offered in institutional settings range from 3 to 31 percent for sex crimes, depending on the study (78,(87)(88)(89)(90)(91). Of the studies that compared treated to untreated subjects, two programs presented lower recidivism rates for treated subjects (87,89,90), and two programs showed no differences (78,91).…”
Section: Outcome Studies Of Cognitive-behavioral Treatmentmentioning
confidence: 99%
“…Some of these factors consist of static factors such as individual characteristics, living alone (Marques, Day, Nelson, & West, 1994), abusive early environments (Seghorn, Prentky, & Boucher, 1987) and past behavioral patterns of sex offending with a range of victims (Prentky, Knight, & Lee, 1997). Other risk factors consist of dynamic or treatable characteristics, such as deviant sexual preferences (Hanson, & Bussiere, 1998), social incompetence (Marshall, Earls, Segal, & Drake, 1983), poor stress management (Marques, et al, 1994;Marshall et al, 1983), cognitive distortions (Ward, Hudson, & Marshall, 1995), avoidance (Prentky, & Knight, 1991), psychopathy (Rice, Chaplin, Harris, & Couts, 1994), lack of motivation, non adherence to treatment (Marshall et al, 1999), and poor problemsolving ability (McMurran, Egan, Richardson, & Ahmadi, 1999;Nezu, Nezu, Dudek, Peacock, & Stoll, 2005).…”
Section: Vulnerability Factors For Sex Offendingmentioning
confidence: 99%
“…Solomon and Ray 1984). However, reference was made to much more rigorous pieces of research, including for example longitudinal studies (Marques et al 1994), studies employing experimental design (Jenkins-Hall 1994), and the seminal work of Yochelson and Samenow (1977) on The Criminal Personality which concluded that the approach to eliminating criminal thinking processes was related to reality therapy and rationalemotive therapy.…”
Section: Introductionmentioning
confidence: 99%